Socio-Economic Determinants of Pan-African Digital Payments Among Small Marketing Businesses - Oloveze, Ambrose; Oteh, Ogbonnaya Ukeh; Obasi, Raymond Ozoemena; Kevin, Chukwuoyims; Onya, Victoria Ogwu; Ibok, Ibok Nkanikpo (Journal of Technology Management and Business, 2024)
Several studies have focused on factors that influence adoption of innovation. Studies demonstrate that all innovations are not the same with innovations serving as unit of analysis in most cases. However, the dearth of empirical literature, the focus of studies on adoption of innovation by SME owners in the south-west Nigeria, and the COVID-19 pandemic effect on SMEs provides a direction for this study in south east Nigeria. Therefore, the study concentrated on the socio-economic determinants of small marketing business on intention to adopt PAPSS in Abia State and Anambra State. Structured questionnaire was used to collect the data from 369 small marketing business owners in different ventures in Abia State and Anambra State. Logistic regression was used to analyse the data. The results demonstrates that gender, education, type of business and experience are significant and have odd ratios of occurrence while experience have the most direct and significant likelihood to occur with additional experience. Therefore, the understanding of the socio-economic factors provides a direction on intention to adopt PAPSS and subsequent adoption.